Janus nanoparticles: New generation of multifunctional nanocarriers in drug delivery, bioimaging and theranostics. (March 2020) - Rahiminezhad, Zahra; Tamaddon, Ali Mohammad; Borandeh, Sedigheh; Abolmaali, Samira Sadat
Graphical abstract: Highlights: Janus nanoparticles (JNPs) are colloidal dispersions with anisotropic nature. Masking, self-assembly, sputtering and microfluidics are used for JNPs synthesis. JNPs incorporates both hydrophobic and hydrophilic drugs simultaneously. JNPs are elaborately modified for molecular targeting and stimuli-responsiveness. JNPs are envisioned for theranostic applications in era of personalized medicine. Abstract: Janus nanoparticles (JNPs) are anisotropic particles composed of two distinct sides with differences in chemical nature and/or polarity on each side. These particles have attracted much attention in recent years due to their dual functionality, anisotropic nature and potential applications in material science and biomedicine such as nanocorals, micro/nanomotors, catalyst, and stabilizers. With the presence of different functional group and various chemical compounds on each side, JNPs can simultaneously be modified for specific needs in drug delivery, such as loading two drugs, grafting with a targeting ligand and imaging agents. Moreover, the site-selective modification of each face allows combining different agents within a single particle without significant interaction, leading to their versatile usage in theranostics. This review discusses the main strategies used for synthesizing JNPs with controllable morphology in a wide range of sizes and surface functionality by highlighting JNPs important properties and applications in the field of drug delivery with a focus on theranostics.